Development of carbon fibre‐reinforced plastic (CFRP) crash absorbers with stable crushing behaviour considering the connection to the bumper system: Entwicklung von kohlenstofffaserverstärktem Kunststoff (CFK) Crashabsorbern mit stabilem Stauchverhalten unter Berücksichtigung der Anbindung an das Stoßfängersystem. Issue 11 (16th November 2016) - Szlosarek, R.; Bombis, F.; Mühler, M.; Kröger, M.; Karall, T.
Abstract : Crash absorbers made of fibre‐reinforced plastics becoming more and more popular to reduce the mass in the front section of cars. Various research projects analysed the high specific energy absorption and the stable crushing behaviour of this material, however without examining the connection to other car body components. This paper focuses on the connection of the crash absorbers to the bumper system, particularly regarding to the crushing behaviour. An initial step focused on the development of a crash absorber made of carbon‐fibre‐reinforced plastic, which shows similar energy absorption compared to absorbers made of aluminium. A following step investigated various connection concepts using a drop tower. These first connection concepts resulted in unstable crushing behaviour. The finite element simulation of the tests delivered additional information about the reasons for the insufficient crushing behaviour. Subsequently, a simulation of various connection concepts turned out suitable connection concepts. A final drop tower test investigated the best connection concept. The developed connection system shows similar to the unmodified crash absorber stable crushing behaviour.